Impacted Maxillary Canines, Premolar and Central Incisor - Surgical Exposure and Orthodontic management (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
The importance of maxillary canine impaction is that it may compromise dental health , particularly because a small but significant proportion of impacted canine is associated with the resorption of the roots of neighbouring teeth. A few cases of impacted upper canines, premolar and central incisors of different ages are presented. Although the best treatment alternative for impacted teeth is extraction, the same cannot be directly applied to canines and central incsor especially. Since canines present with them a high demand on aesthetic and functional requirements. Thus, alignment of impacted canines into the arch is the best treatment approach. The purpose of this study is to evaluate the impacted maxillary canines that were surgically exposed, followed by orthodontic alignment into occlusion. DOI: http://dx.doi.org/10.3329/bjodfo.v1i1.15975 Ban J Orthod & Dentofac Orthop, October 2010; Vol-1, No.1, 24-26